Scaling up financial and capacity resources for nutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Scaling up actions and interventions to improve nutrition requires financial resources backed up by individual, organizational, and system capacity to plan for impact, refine interventions, and expand coverage while maintaining quality. This chapter focuses on these intertwined issues, with a strong emphasis on reducing undernutrition.